2001
DOI: 10.1021/es010638q
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Quartz Addition on the Mechanochemical Dechlorination of Chlorobiphenyl by Using CaO

Abstract: Grinding a mixture of 3-chlorobiphenyl (BP-Cl) and CaO with or without the addition of quartz was conducted in air by a planetary ball mill to investigate the mechanochemical dechlorination of BP-Cl. The dechlorinating reaction proceeds with an increase in grinding time, and over 99% of BP-Cl is decomposed at 360 min. Washing the ground sample with different solvents results in different products. Addition of quartz to the grinding mixture facilitates dechlorination efficiency, especially in the case of a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…Many previous literatures [7,9,11] shown that the dechlorination mechanism was mainly engaged in degradation of chlorinated organic compounds. To see how far the chlorination of PCDD/Fs has proceeded, we calculated the degree of chlorination of PCDD/Fs d c by Eq.…”
Section: The Degrees Of Chlorination For Pcdd/fs In MC Treated Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Many previous literatures [7,9,11] shown that the dechlorination mechanism was mainly engaged in degradation of chlorinated organic compounds. To see how far the chlorination of PCDD/Fs has proceeded, we calculated the degree of chlorination of PCDD/Fs d c by Eq.…”
Section: The Degrees Of Chlorination For Pcdd/fs In MC Treated Samplementioning
confidence: 99%
“…A mechanochemical (MC) method has recently attracted attention as a simple route for treating chlorinated organic compounds, including 4-chlorobiphenyl, octachlorodibenzop-dioxin and octachlorodibenzofuran [7], 4-chloroaniline, pentachlorophenol, polychlorinated biphenyls [8], 1,2,3-trichlorobenzene [9], polyvinyl chloride (PVC) [10], 3-chlorobiphenyl [11], hexachlorobenzene [12] and DDT [13]. MC treatment is a non-combustion technology that requires no heating process or off-gas treatment, which is notable advantage over the conventional heating processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hall et al [17] found that after 12 h of mechanochemical reaction of DDT with CaO, no organic materials was detected by GC-MS. Zhang et al [18] demonstrated that over 99 % of 3-chlorobiphenyl was decomposed by co-grinding 3-chlorobiphenyl with CaO for 6 h. And Zhang et al [19] also found that almost 100 % of debromination was achieved by grinding CaO with hexabromobenzene. Lu et al [20] found that the degradation rate reached 99.0 % by grinding 2,4,6-trichlorophenol with the mixture of calcium oxide and SiO 2 for 6 h. However, when CaO was used as additive for mechanochemical degradation of POPs, the complete degradation of POPs taken a long time.…”
Section: Introductionmentioning
confidence: 99%
“…samples effectively. From the additives investigated [1][2][3][4][5][6][7][8], complete decomposition of PVC was achieved with CaO within 2 h of grinding. Under similar experimental conditions, more than 95% of Cl in PVC was removed by CaCO 3 and Ca(OH) 2 in 4 and 12 h, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of functions for grinding and designing an ideal mill to exhibit a high grinding efficiency are worth consideration, but not easy to realize soon. Selecting new additives for the decomposition of chlorinated compounds is another route and has been discussed by various researchers [4][5][6]8]. Lee and co-workers [9,10] report their findings on the mechanochemical synthesis of LaOF from poly(vinylidene fluoride) and LaOX (X=Cl, Br) from LaCl 3 and LaBr 3 using La 2 O 3 as a rare earth oxide additive.…”
Section: Introductionmentioning
confidence: 99%